2013
DOI: 10.5194/acp-13-6403-2013
|View full text |Cite
|
Sign up to set email alerts
|

Air–snow transfer of nitrate on the East Antarctic Plateau – Part 1: Isotopic evidence for a photolytically driven dynamic equilibrium in summer

Abstract: Abstract. Here we report the measurement of the comprehensive isotopic composition (δ15N, Δ17O and δ18O) of nitrate at the air–snow interface at Dome C, Antarctica (DC, 75°06' S, 123°19' E), and in snow pits along a transect across the East Antarctic Ice Sheet (EAIS) between 66° S and 78° S. In most of the snow pits, nitrate loss (either by physical release or UV photolysis of nitrate) is observed and fractionation constants associated are calculated. Nitrate collected from snow pits on the plateau (snow accum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

44
396
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(443 citation statements)
references
References 47 publications
44
396
3
Order By: Relevance
“…Model calculations are constrained and validated with existing observations of atmospheric NO (Erbland et al, 2013). The diurnal temperature variation is ∼ 10 K in summer, spring (midSeptember until mid-November) and autumn (February to March).…”
Section: Model Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Model calculations are constrained and validated with existing observations of atmospheric NO (Erbland et al, 2013). The diurnal temperature variation is ∼ 10 K in summer, spring (midSeptember until mid-November) and autumn (February to March).…”
Section: Model Validationmentioning
confidence: 99%
“…The relative contribution of photochemical and physical processes has been a matter of debate (Röthlisberger et al, 2000). Isotopic studies have shown that photolysis of NO − 3 is the dominating loss process of NO − 3 in snow (Frey et al, 2009;Erbland et al, 2013). Based on a typical photolysis rate coefficient of nitrate, J NO − 3 ≈ 1 × 10 −7 s −1 (at the surface in Dome C at a solar zenith angle of 52 • , France et al, 2011), the characteristic time for nitrate photolysis is ∼ 10 7 s. Thus, the characteristic time of nitrate photolysis is much larger compared to other physical processes near the snowpack surface, such as grain surface adsorption and solid-state diffusion (Table 1).…”
Section: Processmentioning
confidence: 99%
“…The relative importance of the photochemical and physical loss processes at a given site is a key issue to improve the interpretation of the nitrate ice core and determine the nitrate transfer function at the air-snow interface. This requires a knowledge of the nitrogen isotopic fractionation constant associated with each loss process [111].…”
Section: Nomentioning
confidence: 99%
“…At Dome C, photolysis should dominate nitrate loss [111] [121]. Field studies in the Antarctic as well as laboratory experiments have shown that the photochemical reduction of nitrates takes place in the superficial liquid-like layer of snow [126] [127].…”
Section: Nomentioning
confidence: 99%
See 1 more Smart Citation